Homeyard Contribution Based on Women Farmer Family Management (KWT) in Rural Areas - Suparwata, Dewa Oka; Ayu Indrianti, Merita; M. Mokoginta, Meity; Gobel, Yusriyah Atikah; Djibran, Moh. Muchlis; A. Hasan, Zuarni (Agrikan Jurnal Agribisnis Perikanan, 2022)
The decrease in the capacity of the yard is often the result of non-agribusiness-based management and inappropriate selection of commodities. This action weakens the function of the home garden ecosystem which also reduces its benefits as an economic, social and environmental aesthetic support. To grow this contribution, KWT has a vital role in generating yard optimization. This paper is to examine the role of KWT in increasing the contribution of the yard in the rural area. The approach used was a survey, which was conducted in Kayubulan Village from August to October 2018. The research sample consisted of 60 people and was analyzed descriptively including analysis of contribution, role, working hours and income. The results showed that 42.42% of the yard area was utilized for the cultivation of vegetables, fruit and spices. The time spent by women farmers is 23.28 JKSP/month, and the contribution of yard management is 54.61%. Yard management is able to contribute IDR 403,175/month equivalent to 15.28%. This indicates that good management of the yard will be able to increase profits by choosing an adaptive pattern, business potential and based on the family's primary needs.